Dye functionalized carbon nanotubes for photoelectrochemical water splitting – role of inner tubes. Issue 7 (2nd February 2016) - Cheng, Yi; Memar, Amir; Saunders, Martin; Pan, Jian; Liu, Chang; Gale, Julian D.; Demichelis, Raffaella; Shen, Pei Kang; Jiang, San Ping
Abstract : Dye functionalized double- and triple-walled carbon nanotubes are effective photoanodes for water splitting without the attachment of semiconductor and water oxidation catalysts. Abstract : Dye sensitized water splitting photoelectrochemical (PEC) cells generally require the attachment of photosensitizer to a semiconductor and a water oxidation catalyst (WOC). Here we report for the first time that dye, including zinc phthalocyanine (ZnPc), cobalt phthalocyanine (CoPc) and tris(bipyridine)ruthenium(ii ) (Rubpy), sensitized or functionalized pristine carbon nanotubes (dye/CNTs) without the presence of semiconducting oxides and conventional WOCs have unusually high activity for PEC water splitting in alkaline solutions under ultraviolet (UV) and visible light. The PEC activities of dye/CNTs show distinctive volcano curves as a function of number of walls with the highest activity observed on double- and triple-walled CNTs (DWNTs and TWNTs). For example, the photocurrent of the ZnPc functionalized TWNTs at 1.2 V vs. RHE is 0.32 mA cm −2, which is ∼4 times of 0.09 mA cm −2 obtained on the ZnPc functionalized single-walled CNTs (SWNTs) and one order of magnitude higher than 0.02 mA cm −2 on ZnPc functionalized multi-walled CNTs (MWNTs). On the other hand, the photocurrents are negligible on pristine CNTs, less than 0.005 mA cm −2 under identical experimental conditions. This remarkable feature is due to the unique charge separation ability of the dye/CNTs, where the photoexcited electrons are transferred to the inner tubes via the electron tunneling under the dc bias voltage, and the significant electrocatalytic activities of DWNTs and TWNTs for the water oxidation reaction. The results provide new opportunities for the development of artificial photosynthetic systems via the manipulation of the quantum properties of CNTs.